KUKTEM employs hands-on approach for undergrads - UMP, . (Utusan Melayu (M) Berhad, 2002)
Kuantan - Without much fanfare, a university college has started its operations here early this year with the objective of producing highly skilled manpower to further catalyse the country's economic growth.